Medico-legal Aspects of Firearm Injury Cases in Agra Region - Kumari, Sangeeta; Rajput, Ajay Singh; Agarwal, Ajay; Arif, Ayesha; Chaturvedi , RK (Journal of Indian Academy of Forensic Medicine, 2015)
Firearm injury is one of the important causes of morbidity & mortality in India. A detailed study of  medico-legal parameters in firearm injuries cases in Agra region is still lacking. The study was conducted  in S. N. Medical College & Hospital, Agra. All the firearm injury cases, from October 2006 to October 2008  were included. Victim’s biological details, motive of injury, type of firearm used, shots, diurnal variation of  injuries, sites of injury, wound examination and cause of death were studied. Out of 1919 injury cases  reported, 240 (12.5%) cases were of firearm injury. In total 240 cases, 90% were male victims and the  most common age group was 11-30 years (71.8%). Shotgun, country made gun known as ‘kattas’, were  used in 60% cases. Single shot was present in most cases 228 (95%). The most common site of injury  was abdomen (30.9%). The fatality rate was 1.2% and hemorrhagic shock (68.9%) as the most common  cause of death. In the present study, homicidal motive was the most common in firearm injuries cases  and shotgun/kattas was the most common weapon used, as it is indigenously manufactured in Agra  region.
Keywords: Firearm injury; Firearms; Homicide; Shotgun